2018
DOI: 10.1016/j.neuroimage.2017.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilingualism on white matter integrity in older adults

Abstract: Bilingualism can delay the onset of dementia symptoms and has thus been characterized as a mechanism for cognitive or brain reserve, although the origin of this reserve is unknown. Studies with young adults generally show that bilingualism is associated with a strengthening of white matter, but there is conflicting evidence for how bilingualism affects white matter in older age. Given that bilingualism has been shown to help stave off the symptoms of dementia by up to four years, it is crucial that we clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 55 publications
2
48
0
3
Order By: Relevance
“…Diffusion tensor imaging (DTI) data were preprocessed using the top-up (41), and eddy (42) pipelines within FSL. WM integrity was assessed via several measurements, including FA, MD, RD, and AD values (43,44). These values were calculated using the FDT and DTIFIT (45) pipelines.…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) data were preprocessed using the top-up (41), and eddy (42) pipelines within FSL. WM integrity was assessed via several measurements, including FA, MD, RD, and AD values (43,44). These values were calculated using the FDT and DTIFIT (45) pipelines.…”
Section: Methodsmentioning
confidence: 99%
“…Pioneering research on white matter tracts by Luk et al ., for example, revealed that bilingual speakers report greater integrity of long‐range tracts in the language network (e.g., the bilateral superior longitudinal fasciculi, right inferior fronto‐occipital fasciculus, and uncinate fasciculus). Anderson et al . showed increased white matter integrity specifically in the left superior longitudinal fasciculus for such older life‐long bilinguals.…”
Section: Bilingualism Healthy Aging and Neuroprotectionmentioning
confidence: 99%
“…These studies report monolingual and bilingual group differences, in a way where healthy older bilingual population exhibit resilience to age‐related neurodegeneration. This resilience is expressed as preservation of grey matter in brain areas implicated in language acquisition and control, such as the dorsolateral prefrontal cortex, anterior cingulate cortex and ATL (Abutalebi et al., , ), the IFG and IPL (Borsa et al., ; Heim et al., ), and the hippocampus (Voits, Robson, Rothman, & Pliatsikas, ), and higher integrity in white matter tracts such as CC, ILF, and IFOF (Anderson et al., ; Gold, Johnson, & Powell, ; Luk et al., ), all regions central to the predictions of the dynamic restructuring model, especially at Stages 2 and 3. All of this adds to the idea of bilingualism as a contributing factor to a neural reserve (i.e., build‐up of structural scaffolding of neural tissue in the brain, supporting it against tissue or synaptic loss).…”
Section: The Dynamic Effects Of Bilingualism and Their Implications Fmentioning
confidence: 99%